The Influence of Incentives, Motivation and Work Discipline on Employee Performance at Credit Union Filosofi Petani Pancur Kasih Pontianak - Alberd Alberd (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2023)
This study aims to analyze the effect of incentives, motivation, and work discipline on employee performance at CU Filosofi Petani Pancur Kasih Pontianak. The instrument test used is the reliability test, validity test, statistical test (T-test, F test, and R2 test/coefficient of determination), and classical assumption test (multicollinearity test, heteroscedasticity test, and normality test). The number of samples was 37 people. This research is very important because it looks at the performance of CU Filosofi Petani Pancur Kasih employees in the last time bracket has decreased and this impact is certainly not good for the development of an organization, The data analysis method used in this study was multiple regression, All populations are 37 people and all of them (census) are sampled in this study to achieve a good level of precision.Partially, the incentive variable does not have a significant effect on the employee performance of CU Filosofi Petani Pancur Kasih Pontianak. However, motivation and discipline have a significant effect on the employee performance of CU Filosofi Petani Pancur Kasih Pontianak. Simultaneously, the Incentive (X1), Motivation (X2), and Discipline (X3) variables significantly influence the employee performance of CU Filosofi Petani Pancur Kasih Pontianak. Based on the analysis of the coefficient of determination, the employee performance of CU Filosofi Petani Pancur Kasih Pontianak can be concluded and explained by the variables of Incentives (X1), Motivation (X2), and Discipline (X3), while the other 52.4% are influenced or explained by other variables which are not discussed in this study.